PEWARNA ALTERNATIF PREPARAT SEDIAAN APUSAN DARAH TEPI (SADT) DARI EKSTRAK BUNGA KAMBOJA (Plumeria rubra L. cv. Acutifolia.) - Ayu Nirmala Sari; Desy Nurrahma Dhani; Alifa Tazkiya; Badratun Nafis; Siti Diah Ayu Lestari Gea; Rizki Fazilah (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2024)
Peripheral Blood Smear Preparation (SADT) is a smear preparation made using human blood that is colored for examination in hematology. This examination is done to see and assess peripheral blood cells such as leukocytes, platelets and erythrocytes. Giemsa has a drawback because methylene blue contained in giemsa can be inhaled causing cyanosis. Azur B content can also cause waste because the material contained is not easily decomposed and eosin content can cause allergic reactions.This study aimed to test the water extract of Cambodian flowers (Plumeria rubra L. cv. Acutifolia.) as an alternative dye of peripheral blood smear preparations. This research is in the form of qualitative research with a method of making purple dye for water extraction of frangipani flowers (Plumeria rubra L. cv. Acutifolia.). Microscopic observations of frangipani flower extract (Plumeria rubra L. cv. Acutifolia.) as a preparation of Edge Blood Smear (SADT) can be used as an alternative natural use besides Giemsa staining, because erythrocytes, leokocytes and platelets are able to bind colors well.